Psychosocial empowerment-based interventions for smoking reduction: concepts, measures and outcomes. A systematic review. (December 2020) - Coppo, Alessandro; Gattino, Silvia; Faggiano, Fabrizio; Gilardi, Luisella; Capra, Paola; Tortone, Claudio; Fedi, Angela; De Piccoli, Norma
Although empowerment is a widely used concept in health-related areas, its definition remains unclear. While there is evidence for the effectiveness of empowerment interventions in improving some psychosocial factors linked to health (e.g. patient self-care strategy, coping skills, access and effective use of health services) and some health outcomes like mental health and HIV/AIDS-related behaviour, other data appear to contradict this. Moreover, concepts, measures, and outcomes related to empowerment are operationalized in different ways. Using the case of tobacco control programmes, we wanted to explore: (a) how research on smoking reduction/prevention has conceptualized empowerment; (b) which measures and instruments have been used to assess behaviour outcomes and the empowerment process. We hypothesized that the transformative potential that characterizes empowerment is marginally considered. A total of 18 studies reporting on the effect of prevention interventions on smoking and/or empowerment outcomes were reviewed. Two kinds of study were distinguished: (a) studies reporting behaviour outcomes without data about the impact on empowerment; (b) studies analysing the empowerment process. Among this latter type, some studies did not provide information about the specific behaviour (smoking), while others examined the impact of intervention on both smoking and empowerment. In about half of all studies, empowerment strategies were found to be effective in improving smoking outcomes, while no differences were found between intervention and control groups in the remaining studies. The present review suggests that pragmatic definitions of empowerment need to be developed in order to promote its transferability and evaluation.